Portraits of Social Strangers - Steve Noble (Adult Education Research Conference, 1999)
This paper discusses the use of art forms, as a way of "teaching and preparing" people experiencing life transitions. The study describes how a gay male graduate student experiences his own recent life shift alongside those explored by two recent immigrant women from Australia and Taiwan to Vancouver, Canada.